Upper Mantle Earth Structure in Africa From Full‐Wave Ambient Noise Tomography. (5th January 2019) - Emry, E. L.; Shen, Y.; Nyblade, A. A.; Flinders, A.; Bao, X.
Abstract: Our understanding of the tectonic development of the African continent and the interplay between its geological provinces is hindered by unevenly distributed seismic instrumentation. In order to better understand the continent, we used long‐period ambient noise full‐waveform tomography on data collected from 186 broadband seismic stations throughout Africa and surrounding regions to better image the upper mantle structure. We extracted empirical Green's functions from ambient seismic noise using a frequency‐time normalization method and retrieved coherent signal at periods of 7–340 s. We simulated wave propagation through a heterogeneous Earth using a spherical finite‐difference approach to obtain synthetic waveforms, measured the misfit as phase delay between the data and synthetics, calculated numerical sensitivity kernels using the scattering integral approach, and iteratively inverted for structure. The resulting images of isotropic, shear wave speed for the continent reveal segmented, low‐velocity upper mantle beneath the highly magmatic northern and eastern sections of the East African Rift System (EARS). In the southern and western sections, high‐velocity upper mantle dominates, and distinct, low‐velocity anomalies are restricted to regions of current volcanism. At deeper depths, the southern and western EARS transition to low velocities. In addition to the EARS, several low‐velocity anomalies are scattered through the shallow upper mantle beneath Angola and North Africa, and some of these low‐velocity anomalies may be connected to a deeper feature. Distinct upper mantle high‐velocity anomalies are imaged throughout the continent and suggest multiple cratonic roots within the Congo region and possible cratonic roots within the Sahara Metacraton. Plain Language Summary: We use advanced seismic imaging techniques (full‐waveform tomography), constrained by data from background (ambient) seismic noise to image the upper mantle beneath the African continent and search for low‐velocity structures (hot spots) that might coincide with regions of volcanism, surface uplift, and continental rifting, particularly along the East African Rift. We also searched for high‐velocity structures (old, rigid blocks) that could influence how warm, buoyant material flows within the Earth's upper mantle. Our seismic tomography method allowed us to obtain a clear image of structure beneath parts of Africa where no or very few seismometers are located (such as the Sahara Desert and the Congo Basin). Our results provide indications for segmented secondary (or shallow) upwellings in the upper mantle beneath East Africa, as opposed to earlier models suggesting one large, continuous plume within the upper mantle. Our results also suggest that the one large, rigid, cratonic block previously imaged beneath the Congo region may instead be composed of smaller, distinct blocks. These results provide insight into the factors that control continental rifting along East Africa and provide new testable models that help us to understand the relationships between upper mantle flow, rifting, volcanism, surface uplift, and sedimentation records. Key Points: Full‐waveform, long‐period ambient noise tomography was used to produce a new isotropic Vs model of the upper mantle beneath Africa Several cratonic fragments have been imaged in the upper mantle, particularly within the Congo Craton Results suggest multiple upwellings beneath Africa, including complex patterns of low‐velocity features beneath the East African Rift System